2012
DOI: 10.1111/j.1464-5491.2012.03638.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ketoacidosis at diagnosis of childhood onset Type 1 diabetes in Wales from 1991 to 2009 and effect of a publicity campaign

Abstract: Over 20 years in Wales there has been no change in the proportion of children with Type 1 diabetes initially presenting with ketoacidosis. This presentation occurs in a higher proportion of new cases aged under 5 years. Publicity to increase awareness did not reduce the proportion with ketoacidosis at diagnosis in Wales. We need to get the educational message through to parents to reduce ketoacidosis at presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 14 publications
5
66
0
1
Order By: Relevance
“…The overall frequency of DKA was found to be stable over time in a study of 14,664 youths in Germany and Austria in the period 1995–2007 (21.1%)3 as well as in another study of 5,615 children in the U.S. in the period 2002–2010 (ranging between 29.1% and 31.1%)17. These studies found that the frequency of DKA did not change over time, even following prevention campaigns, such as those conducted in Austria in 1989–20115 and in Wales in 1999–200122. In a Finnish population-based study in 585 children, a relative reduction of DKA, particularly among children <5 years of age, was observed in the period 1981–200121.…”
Section: Discussionmentioning
confidence: 75%
“…The overall frequency of DKA was found to be stable over time in a study of 14,664 youths in Germany and Austria in the period 1995–2007 (21.1%)3 as well as in another study of 5,615 children in the U.S. in the period 2002–2010 (ranging between 29.1% and 31.1%)17. These studies found that the frequency of DKA did not change over time, even following prevention campaigns, such as those conducted in Austria in 1989–20115 and in Wales in 1999–200122. In a Finnish population-based study in 585 children, a relative reduction of DKA, particularly among children <5 years of age, was observed in the period 1981–200121.…”
Section: Discussionmentioning
confidence: 75%
“…A similar campaign in Australia using HCP education sessions, posters, radio and newspaper adverts and provision of blood glucose testing equipment to HCPs also reported a significant decrease in DKA at diagnosis 30. By contrast, a Welsh campaign using posters in primary care surgeries and radio broadcasts, but without provision of equipment or education, failed to reduce DKA incidence 7. It is possible that the differences in healthcare systems contributed to the variable success of these campaigns; Italy has primary care paediatricians, and in Australia, patients do not have a named primary care practitioner.…”
Section: Discussionmentioning
confidence: 96%
“…Three intervention studies aiming to reduce the incidence of DKA at diagnosis have had varying success 7 29 30. In Italy, Vanelli et al identified that secondary enuresis and nocturia can be early and frequent symptoms of T1DM and, therefore, used this in a poster campaign targeted towards HCPs, teachers and parents.…”
Section: Discussionmentioning
confidence: 99%
“…39 Posters were sent to every pharmacy, school, and general practitioner surgery across Wales, and the campaign publicized with radio interviews. Before the campaign, the risk of DKA was approximately 25% from 1991 to 2009, with no temporal change.…”
Section: Protective Factorsmentioning
confidence: 99%